Role of Clean Technology in Sustainable Manufacturing - Agrawal, Manoj Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sustainable manufacturing is the backbone for the development of standard of living of the country along with its industrial growth. It is a process for meeting development needs while maintaining the stability, integrity and beauty of natural biotic systems such that societal consumption of natural resources is incommensurate with the rate which the nature can replenish itself. It can be more cost and time efficient, especially for small scale production and customized products. In order to have complete and efficient structure of sustainable manufacture it must produce green products by using clean technologies. The manufacturing industries which can integrate the aspect of clean technologies in their technical and financial decisions will hold an important role in winning the everlasting future race. The main objective of this paper is to elaborate the concept and implementation of clean technologies in sustainable manufacturing which includes the process, models and impact assessment of green technologies. The ideas presented in this paper will be quite useful for the researchers and industrialists who are interested in the field sustainable manufacturing.